A haplotype variant of Hu sheep follicle‐stimulating hormone receptor promoter region decreases transcriptional activity. (15th May 2019) - Du, X.; Guo, J.; Cao, Q. Y.; Yao, W.; Li, Q. F.
Summary: In sheep, increased expression of the follicle‐stimulating hormone receptor ( FSHR ) in the ovary is a common feature of ewes that carry the prolific allele. In this study, we demonstrated that polymorphisms in the core promoter of the FSHR gene are associated with the reproductive performance of Hu sheep and are involved in the transcriptional activity of FSHR . An approximately 1.5‐kb region of the 5′ flanking sequence of the Hu sheep FSHR gene was isolated and characterized, and its core promoter was located in the 5′ regulatory region, from nucleotides –580 to –342. Four variants (c.–518T>C, c.–466C>T, c.–414A>G and c.–365C>T) were detected in this region, and six genotypes and three haplotypes were found in the Hu sheep population ( n = 245). An association analysis revealed that these polymorphisms are associated with the litter size of Hu ewes. Furthermore, a luciferase assay showed that the T‐C‐A‐C‐ and C‐T‐G‐T‐type core promoters have higher transcriptional activity than does the T‐C‐G‐C type. Notably, the putative binding site for the transcription factor Yin Yang 1 (YY1) was present at the A allele of nucleotide –414, but YY1 can significantly increase the transcriptional activity of the FSHR core promoter, which contains three different haplotypes. Taken together, our results establish that these variants might be involved in regulating the transcriptional activity of FSHR and litter size in Hu ewes and may provide a novel candidate marker for marker‐assisted selection in sheep breeding.